2010
DOI: 10.1007/s00284-010-9779-y
|View full text |Cite
|
Sign up to set email alerts
|

Nematicidal Activity of a Nonpathogenic Biocontrol Bacterium, Pseudomonas chlororaphis O6

Abstract: Bacterial culture filtrates of an aggressive rhizobacterium, Pseudomonas chlororaphis O6, displayed strong nematicidal activity. The nematicidal activity of P. chlororaphis O6 was markedly reduced in the gacS mutant of P. chlororaphis O6 grown in the presence of glycine, but no reduction of nematicidal activity in the gacS mutant was noted in the absence of glycine. The results of bioassay with P. chlororaphis O6 mutants showed that phenazine and pyrrolnitrin production was not a major factor, but the effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 20 publications
1
30
0
2
Order By: Relevance
“…strain ZE36 on nematodes was not directly tested. Work with Pseudomonas chlororaphis O6 implicated hydrogen cyanide in the suppression of the root-knot nematode Meloidogyne hapla by noting the glycine-dependent nature of the inhibition (Lee et al 2011). Glycine is a precursor to cyanide formation (Wissing 1974).…”
Section: Invertebrates Influenced By Cyanide Of Bacterial Originmentioning
confidence: 99%
“…strain ZE36 on nematodes was not directly tested. Work with Pseudomonas chlororaphis O6 implicated hydrogen cyanide in the suppression of the root-knot nematode Meloidogyne hapla by noting the glycine-dependent nature of the inhibition (Lee et al 2011). Glycine is a precursor to cyanide formation (Wissing 1974).…”
Section: Invertebrates Influenced By Cyanide Of Bacterial Originmentioning
confidence: 99%
“…In pathogens, the Gac sensor kinase system controls virulence gene expression (Heeb and Haas, 2001). It is also found that the Gac/Rsm system of PcO6 is required for the expression of the insecticidal activity to the tobacco hornworm (Rangel et al, 2016), and to the root knot nematode (Lee et al, 2011(Lee et al, , 2017. In addition, the Gac system is shown to be important in expression of gene expression in the inhibition of fungal growth by PcO6 Oh et al, 2013a;Park et al, 2011).…”
Section: Gac/rsm System a Master Switch For Global Regulationmentioning
confidence: 99%
“…Hosts other than plants also are affected by colonization with PcO6, because this bacterium possessed insecticidal capacity. This bacterium showed insecticidal activity on the tobacco hornworm (Rangel et al, 2016) and on nematodes (Lee et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The antifungal agents include hydrogen cyanide (HCN), siderophores, biosurfactants and antibiotics, and enzymes including proteases, lipases, chitinases, and glucanases (Dubis et al, 2007; Haas and Defago, 2005; Raaijmakers et al, 2002). The root colonizer Pseudomonas chlororaphis O6 produces several compounds with antifungal activity including a pyoverdine-like siderophore, phenazines, pyrrolnitrin and HCN (Kang et al, 2007; Lee et al, 2011; Park et al, 2011). Effective root colonization by P. chlororaphis O6 also protects plants from pathogens through induction of systemic resistance against various plant diseases as well as drought and salinity stress (Cho et al, 2008; 2012; Han et al, 2006).…”
mentioning
confidence: 99%